2022
DOI: 10.1126/scitranslmed.abb7695
|View full text |Cite
|
Sign up to set email alerts
|

Blocking UBE2N abrogates oncogenic immune signaling in acute myeloid leukemia

Abstract: Dysregulation of innate immune signaling pathways is implicated in various hematologic malignancies. However, these pathways have not been systematically examined in acute myeloid leukemia (AML). We report that AML hematopoietic stem and progenitor cells (HSPCs) exhibit a high frequency of dysregulated innate immune-related and inflammatory pathways, referred to as oncogenic immune signaling states. Through gene expression analyses and functional studies in human AML cell lines and patient-derived samples, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…In prior studies, we found that UBE2N is required for leukemic cell function in vitro and in vivo by maintaining oncogenic immune signaling states. 58 UBE2N (Ubc13) is a ubiquitin-conjugating enzyme implicated in the regulation of TRAF6, an E3 ubiquitin ligase and effector of the TLR/IL1R signaling pathway. 59 Using small-molecule inhibitors identified in in silico structure-based and cellular-based screens, we revealed the therapeutic efficacy of interfering with UBE2N function by blocking of ubiquitination of innate immune- and inflammatory-related substrates in human AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, we found that UBE2N is required for leukemic cell function in vitro and in vivo by maintaining oncogenic immune signaling states. 58 UBE2N (Ubc13) is a ubiquitin-conjugating enzyme implicated in the regulation of TRAF6, an E3 ubiquitin ligase and effector of the TLR/IL1R signaling pathway. 59 Using small-molecule inhibitors identified in in silico structure-based and cellular-based screens, we revealed the therapeutic efficacy of interfering with UBE2N function by blocking of ubiquitination of innate immune- and inflammatory-related substrates in human AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts are being pursued to restore normal innate immune signaling in MDS HSCs 23,[57][58][59][60][61] . One approach has been to inhibit IRAK4 in MDS 21 .…”
Section: Discussionmentioning
confidence: 99%
“…CD81 has been associated with a poor prognosis in AML (53) and is also a known marker in B-ALL (54, 55) while the E2 family of a ubiquitin-conjugating enzyme, UBE2s has a role in the cell cycle progression (56). AML cells are dependent on UBE2N-dependent oncogenic immune signaling states (57). DEG-associated pathway analysis showed that Sirtuin signaling, p38 MPAK signaling, and PI3K signaling were upregulated in B/My MPAL blasts.…”
Section: Discussionmentioning
confidence: 99%